A CURSORY EVALUATION OF THE SITUATION OF HIGHER EDUCATION FUNDING IN SELECTED AFRICAN COUNTRIES (Journal of Association of Educational Management and Policy Practitioners, 2024)
This paper is a cursory evaluation of the situation of higher education funding in selected African countries. It is a library research paper that discussed the funding situation in selected African countries. It considered the roles of higher education in national development. It was discovered that most of the African nations use a cost-sharing or partial support model which demands the participation of beneficiaries (household. government, community). The discussion shows that no single funding model should cushion the challenge of higher education rather it calls for a combination of models. The following suggestions among others were made: policies should be properly studied before implementation, services of education managers should be properly and adequately engaged and utilized, obsolete and irrelevant course of studies should be struck off, and synergy between school and investors encouraged.